The Effect of Institutional Ownership, Company Size, Profitability, and Tangibility on Capital Structure in Non-Cyclical Consumer Sector Companies Listed on The Indonesia Stock Exchange - Putrandy, Leonardo; Santoso, Hadi (Research Center and Case Clearing House PPM School of Management, 2026)
This study aims to examine the effect of these variables on the capital structure of non-cyclical consumer sector companies listed on the Indonesia Stock Exchange. This study employs a quantitative approach using secondary data obtained from firms’ financial statements for the period 2018–2022. The sample was selected using a purposive sampling method, resulting in 67 companies with a total of 335 observations. The data were analyzed using panel data regression. The results show that institutional ownership has a positive and significant effect on capital structure, while profitability has a significant negative effect. Meanwhile, firm size and tangibility do not have a significant effect on capital structure. These findings support agency theory and pecking order theory in explaining corporate financing decisions. Practically, the findings provide insights for managers and investors in determining optimal financing strategies. Theoretically, this study contributes to the literature on capital structure determinants in companies operating in emerging markets